2019
DOI: 10.12659/ajcr.918918
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Status Epilepticus and Transient Stress Cardiomyopathy Associated with Smoking the Synthetic Psychoactive Cannabinoid, UR-144

Abstract: Patient: Female, 19-year-oldFinal Diagnosis: Status epilepticus and stress induced cardiomyopathySymptoms: SeizureMedication: —Clinical Procedure: —Specialty: ToxicologyObjective:Unusual clinical courseBackground:Synthetic cannabinoids have a higher affinity for the cannabinoid receptors CB1 and CB2 than natural cannabinoids. Their use can be associated with cardiovascular disease and neurological complications. A case is reported of status epilepticus and stress cardiomyopathy following the recreational use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In this literature review, it was found that stress cardiomyopathy is more common after convulsive status epilepticus [ 9 - 24 ]. A STAT echocardiogram is very important in order to assess the myocardial injury and to have baseline imaging results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this literature review, it was found that stress cardiomyopathy is more common after convulsive status epilepticus [ 9 - 24 ]. A STAT echocardiogram is very important in order to assess the myocardial injury and to have baseline imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…The time to resolution also remains unknown, as we do not know the exact left ventricular recovery mechanism, therefore close follow-up with repeat TTE is important. From our review, it was found that the time of normalization ranges from four days to about eight weeks [ 9 - 24 ]. The prevalence of SCM secondary to SE is much more common in women, especially postmenopausal women [ 9 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…o.) [2,11]. Akutes Nierenversagen ist eine weitere Komplikation nach SCRA-Konsum, die von Flankenschmerz, Proteinurie, Hämaturie und auch Rhabdomyolyse begleitet sein kann [52].…”
Section: Komplikationen Und Unerwünschte Wirkungenunclassified
“…Several classes of compounds acting as CB2R agonists have been developed in the past years, bearing different scaffolds: dibenzopyran, , oxoquinoline, naphthyridinone, quinolinedione alkyloxy-coumarin indole, indazole imidazopyridine, imidazopyrazine, benzimidazole, , purine, , thiophene, , triazine, , pyridinone, biphenyl, , proline, , and piperidine . In Figure the most representative and selective known CB2R ligands are reported along with their K i values on CB1R and CB2R.…”
Section: Cb2r Agonists: the Proposed Pharmacophorementioning
confidence: 99%